193 Impact of Glucocorticoid Induced Reprogramming on Functional, Histological and Molecular Signalling in the Adult Zebrafish Heart. (6th June 2015) - Wilson, Kathryn; Baily, James; Tucker, Carl; Vass, Sharron; Moran, Carmel; Chapman, Karen; Mullins, John; Kenyon, Chris; Hadoke, Patrick; Denvir, Martin
Abstract : Introduction: Foetal over-exposure to glucocorticoids (GC) has been associated with cardiovascular disorder in later life however the impact of transient early life alterations in GC activity on the heart itself has not been widely studied. We explored this using short term pharmacological and molecular modification of GC activity during the first 120 h of development in the zebrafish by assessing short and long term effects on the structure, function and molecular composition of the heart. Methods: Zebrafish embryos (ZFe) were incubated in dexamethasone (Dex) during the first 120 h post fertilisation (hpf) or underwent injection of eggs with a targeted glucocorticoid receptor (GR) morpholino knockdown (GR MO). Embryos surviving to 120hpf (>90%) were then allowed to develop to adulthood under normal conditions. Cardiac function was assessed at 120hpf by ejection fraction, ventricle cardiomyocyte number (DAPI staining), histology and qPCR. Adult hearts were assessed using cardiac ultrasound (VisualSonics), histology and qPCR at 120 days post fertilisation. Results: In the embryo (120 hpf), Dex-treatment resulted in larger hearts (Dex 107.2 ± 3.1 vs. controls 90.2 ± 1.1 µm, p < 0.001) with higher expression of ventricular myosin heavy chain ( vmhc ) and insulin like-growth factor ( igf ). These hearts displayed a more mature muscle striation pattern with larger, fewer cardiomyocytes, greater ventricle stroke volume and cardiac output compared to controls. Adult hearts (120 days) derived from Dex-treated embryos were heavier (corrected for total body weight 1.02 ± 0.07 µg/mg vs controls 0.63 ± 0.06 µg/mg, p = 0.0007) with increased vmhc mRNA compared to controls. In contrast, GR knockdown with morpholino resulted in smaller hearts with fewer cardiomyocytes, less mature striation pattern, reduced cardiac function and reduced levels of vmhc and igf mRNA in ZFe compared to controls. Adult hearts derived from GR MO embryos were smaller with reduced myocardium wall thickness and increased ventricular cavity area (20.32 ± 1.24% vs controls 11.89 ± 1.22%, p < 0.001) with reduced expression of vmhc . Echocardiography of adult hearts revealed altered Doppler ventricle-inflow patterns in GR Mo but not Dex adults. Conclusions: Short-term alterations in GR activity during embryonic development result in altered structure, function and molecular signalling in the heart with effects maintained into adulthood. These findings point to a mechanism by which foetal GC induced reprogramming could influence reprogramming could influence susceptibility to adult disease.